Knowledge Management of Traditional Batik in Central Java - Sediyono, Eko; Mahatma, Tundjung; Arianti Hunga, Ina (International Journal of Engineering and Technology, 2018)
The Central Java is known as one of the important centres of batik development, and several towns and cities in the region are closely associated with batik. Those may include Pekalongan, Surakarta, Lasem, Pati, Tuban, and Semarang. Batik centres help with the sustainable development of batik in Indonesia, but –especially nowadays, efforts need to be made to pass the knowledge and skills of creating batik, so as to make it interesting, attractive, and easy. Besides, efforts are needed to retain and sustain the cultural heritage so that the Indonesian original products remain in the possession of the nation. The WIKI model enables anybody to become a contributor, putting the thoughts on batik in writing, onto the prepared WIKI. This paper discusses the application of a knowledge management method –such that of WIKI’s– that is put forward by Ikujiro Nonaka, the formulation of which is known as SECI. The good documentation of both tacit and explicit objects may enable the step-by-step tracing of knowledge, so that the original source of knowledge is known. This study also adapts a design to retrieve local knowledge and communal identity created by Chuenrudeemol, focusing on aspects of artistic, social and cultural values, and also economic values, with respect to domestic and gender issues.